Treatment of acute exacerbations of trigeminal neuralgia in the emergency department - a retrospective study - Alexandra Isabel dos Santos Gomes (2022)
Background: Trigeminal neuralgia (TN) is characterized by recurrent and intense pain paroxysms. Some patients experience severe acute exacerbations requiring emergency department (ED) admission. The optimal management of these episodes is not well established. Methods: We performed a retrospective analysis of TN exacerbations in adults admitted to the ED of a tertiary centre. We analysed demographic and clinical data, including pharmacological management in the ED. Results: We included 197 episodes; most patients were females (61%) with a median age of 63 years old. TN exacerbations were treated with opioids in 78% events, nonsteroidal anti-inflammatory drugs in 42%, corticosteroids in 21%, IV phenytoin in 18% and IV lidocaine in 6%. Pain relief was satisfactorily accomplished in 73% cases, partial in 22% and 5% had no pain relief. Sixty-three of the treated patients needed more than one drug to achieve at least partial pain control. IV phenytoin allowed total pain relief in 61% of cases. Conclusion: In our cohort, acceptable pain relief was accomplished in most acute TN exacerbations. Opioids were the most used therapeutical approach. Most events managed with IV phenytoin reached total pain relief. Prospective studies are needed to guide the treatment of acute exacerbations of TN.